Comparison of an alcohol-based hand rub and water-based chlorhexidine gluconate scrub technique for hand antisepsis prior to elective surgery in horses - da Silveira, Eduardo Almeida (Can Vet J, 2016)
This prospective clinical study evaluates the effectiveness of an alcohol-based hand rub (Avagard™) for pre-surgical hand antisepsis in an equine hospital and compares it with traditional scrubbing technique using 4% chlorhexidine gluconate sponges and water. Prior to elective surgery, 3 board-certified surgeons were randomly assigned to hand antisepsis with either technique. Culture samples of each hand were taken at 4 times: before and after neutral soap hand wash, after scrub or rubbing technique, and after surgery. There was no significant difference in mean bacterial colony forming units between scrub and rub techniques over the 3 time periods (P = 0.6), controlling for initial counts. One horse from the scrub group had a skin incision infection following stifle arthroscopy; this was resolved with medical treatment. The alcohol-based hand rub is equivalent in efficacy for pre-surgical hand antisepsis to traditional water-based scrubs in an equine hospital setting.